2006
DOI: 10.1002/tl.254
|View full text |Cite
|
Sign up to set email alerts
|

The development of adaptive expertise in biotransport

Abstract: This chapter describes a model for continuous development of adaptive expertise, including growth along the dimensions of innovation and knowledge, examined in the context of a biotransport course in biomedical engineering. Students improved on both knowledge and innovation, moving along a continuum toward adaptive expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…A level of expertise that is flexible enough to function in novel situations is known as adaptive expertise (Hatano, 1988). Martin, Petrosino, Rivale, and Diller (2006) showed that challenge-based instruction (CBI) is effective in developing adaptive expertise in engineering problem solving. In this paper, we examine the effects of in-service high school math and science teachers participating in a six-week summer professional development course, the Engineering Summer Institute for Teachers (ESIT).…”
Section: Introductionmentioning
confidence: 99%
“…A level of expertise that is flexible enough to function in novel situations is known as adaptive expertise (Hatano, 1988). Martin, Petrosino, Rivale, and Diller (2006) showed that challenge-based instruction (CBI) is effective in developing adaptive expertise in engineering problem solving. In this paper, we examine the effects of in-service high school math and science teachers participating in a six-week summer professional development course, the Engineering Summer Institute for Teachers (ESIT).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results from the use of the survey suggested that adaptability increases the longer a student is in school (freshman to senior). Martin and colleagues [6] found increases over the course of a semester, further supporting the influence of time in academia on the development of adaptive expertise. Results from the survey have also been found to be consistent with interview results.…”
Section: A the Adaptive Expertise Beliefs Surveymentioning
confidence: 85%
“…An empirical longitudinal study was conducted to measure adaptive expertise [6] . This study was later trailed by two follow up studies [14] .…”
Section: Adaptive Expertise In Engineering Educationmentioning
confidence: 99%
“…The optimal techniques used to develop these skills have been widely researched, but a definitive solution remains elusive. 14,20,23,[28][29][30]34,[43][44][45][46][47][48][49][50][51][52] While utilization of a variety of approaches will likely produce optimal development of these skills, active, student-centered, and inquirybased learning appear to be common themes amongst the critical thinking literature. 4 One such activity that promotes active, student-centered, and inquiry-based learning for undergraduate students is the undergraduate research experience.…”
Section: Introductionmentioning
confidence: 99%